Perilaku Penurunan Tanah Terhadap Dry Side of Optimum dan Wet Side of Optimum pada Kepadatan Tanah Organik - Pratama, Dony Rizky; Setyanto, Setyanto; Jafri, Muhammad (Universitas Lampung, 2015)
The decline in soil organic matter due to the burden of its own soil and building construction thereon are not able to with stand the load that lasts. Of these conditions need to know the factors thataffect soil instability, through soil behavior can be observed with the organic content of the soilwater content. The compaction is the beginning of the formation process for testing the strength ofthe soil, so that the pattern of behavior can be identified by soil Dry and Wet Side of Optimum Sideof Optimum.Soil test results Decrease Behavior Against Dry and Wet Side of Optimum Optimum At the Side ofOrganic Soil density, Dry Side of Optimum sample / sample with 5% dry compaction over the bestsample for the fastest processing speed and magnitude of soil degradation as well as the smallestdecrease in the reduction process quickly said to be good for the soil more quickly reach the soillayer in a stable condition and the magnitude of the smallest drop is quite good because thecompression process a smaller type of soil, thereby reducing the risk of damage to the constructionthereon that the Cv value obtained by 0,168cm 2 / sec, Cc for 2.33, and AV 0.28 cm 2 / sec.Keywords: Organic Soil, Compaction, Dry Side of Optimum, Wet Side of Optimum, and SoilDeclinel.